OFR-126-84 Investigation Of Blast-Induced Underground Vibrations From Surface Mining - Introduction - Background - Michael K. Phang (The National Institute for Occupational Safety and Health (NIOSH), 1984)
The use of explosives to fragment rock generates ground vibrations which may have a detrimental effect on contiguous underground coal mine openings. Increased surface blasting by a burgeoning number of surface coal mines and quarries has caused considerable concern among underground mine operators. Ground vibration effects generated from surface mine blasting are also causing public concern. In response to this concern, the U.S. Bureau of Mines (Stagg and Engler, 1980) has measured and analyzed ground vibrations and their effects on underground and surface structures. Some of the complaints registered against the mining industry are claims of substantial material damage from vibrations generated by the blasting; others are nuisance complaints of minor damage or annoyance. In general, allegations of damage from surface blasting have been sufficiently numerous to constitute a major problem for mine operators engaged in blasting operations. They have recognized the need for more technological data to evaluate the vibration problems associated with blasting. Both the operators and the general public need adequate safeguards based upon factual data to protect their specific interests. The coal mine industry needs reliable information from which to change blasting operations to reduce the number and severity of major damage claims and eliminate the growing number of nuisance complaints. The problem is of major concern not only to coal mine operators and nearby property owners, but also to federal, state and local governments. At the same time, environmental control agencies responsible for blasting and explosives use require reasonable and appropriate guidelines to protect the miners' lives.